Migrant integration in the EU. The role of place-based policies - Carlotta Fioretti; Paola Proietti; Guido Tintori (European Journal of Spatial Development)
This special issue examines the integration of migrants at the local level by investigating the European Union's role in this context through place-based policies. Traditionally, migration policy has Europeanized, while migrant policy has become more local. This special issue explores also how local authorities contribute to the governance of migrant integration policies beyond mere implementation. It highlights the EU's recognition of cities in this process and investigates EU-funded policies for urban and local development that foster migrant inclusion. The contributions feature case studies from various territories and underscore the role of place-based policies in promoting migrant integration, agency and citizenship. These insights are particularly relevant in the context of Southern European countries, which have unique migration dynamics.